Investing in open access at the University of Minnesota - Allison Langham-Putrow; Emma Molls; Sunshine Carter; Amy Riegelman (Insights: The UKSG Journal, 2024)
The University of Minnesota (UMN) is a large, public institution in the United States. The UMN Libraries has a long history of supporting open access (OA), going back as far as the mid-1990s, and we expanded this support through the creation of an OA investment fund in Fiscal Year 2020. The fund is treated like any other collections fund, ensuring we have a budget specifically marked for investments in OA. As the OA movement has progressed, it has become clear that not all approaches to OA are working in the way they were originally imagined. Potential investments are evaluated on criteria based on our Libraries values and principles around OA, which are outlined in a statement endorsed by campus governance groups. To date, the fund supports a variety of investments, including infrastructure, diamond OA journals and OA monograph programs – OA models that we believe are sustainable and which align with our values of equity more effectively than APC-based publishing models. The budget has grown each year, both through direct allocations and organically, such as when existing journals shift to OA models.